In the shadow of the Caesars Jewish life in Roman Italy - Rocca, Samuel 1968- (Brill, 2022)
The main contribution of this book is that it tries to determine how the Jews answered the challenges of Roman society. Thus, the book presents a refreshing approach to the nature of the Roman attitude toward Judaism and the Jews. In addition, it provides the first detailed examination of the demography and geography of the Jewish communities in Roman Italy. The book also offers a new look at the legal standing of the Jewish communitarian organization. Last but not least, this study also addresses the various facets of the culture of the Jews living in Roman Italy.
Literaturverzeichnis: Seite [285]-316
Keywords: Sozialgeschichte; Juden; Judentum; Römisches Reich; History